Transient Analysis of Current Transformers - Ghumman, Muhammad Ramzan (2001)
The objective of the present work is to investigate the performance and transient behavior of conventional electromagnetic current transformers in comparison to the unconventional current transducers during power system faults. The research has been carried out using PSPICE simulation tools and experimental testing of current transducers. Different types of transducers considered in this research include normal electromagnetic current transformers (EMCT) and its various types, Hall effect current transformers (HECT) and Opto-couplers. The simulation results have shown that electromagnetic current transformers (EMCT) can suffer from transient saturation during high frequency disturbances or permanent saturation during high fault currents. The electromagnetic current transformers (EMCT) were found to saturate above 20 kHz current surges whilst the Hall effect current transducers (HECT) were found to work up to several 100 kHz. The transformation capability of opto-coupler current transducers, using LED/Si based opto-coupler, was found to be more than 1 MHz. It was estimated that a laser and avalanche photo-detector (APD) based magnetooptic current transformer (MOCT) could effectively translate 1 GHz frequency surges. The simulation results have been experimentally tested and found to be correct within the accuracy resolution of available test and measurement equipment. Based on this work it is safe to declare that EMCT can be used for normal monitoring and measurement applications in utility. It is not good for the reliable protection and control application. Anyway, it does not compete the alternate options such as HECT and MOCT in protection and control applications regarding bandwidth, rise time and fault current diagnostics.